Varietal screening and inheritance of resistance to brown spot disease in rice (Oryza sativa) - PRASAD, K; SHUKLA, V D; SINHA, P K (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted to identify the new resistant varieties of diverse origin and inheritance of genes controllingbrown spot disease. Rice (Oryza sativa L.) varieties (560) from diverse sources were screened during wet seasons of1990 and 1991 for brown spot (Cochilobolus miyabeanus Ito & Kuribayashi) disease in the field under natural infectionwhere high disease pressure was created by cultural operations. Twenty-two varieties were identified to be resistantto this disease. The inheritance of resistance was studied during 1992-94 in 6 crosses involving 3 resistant parentsand 1 susceptible parent. It was found that resistance to brown spot disease was controlled by 2 pairs of recessivegenes. The 3 resistant parents 'RR 35-4-1','RR 20-5' and 'RR 36-141 ' had single recessive gene in each. Gene presentin 'RR 20-5' and 'RR 36-141' was the same whereas gene present in 'RR 35-4-1' was different from other 2 resistantparents.